Diatom analysis in Santa Cruz Central Massif (Patagonia, Argentina): Preliminary Results - Fernández, Marilén (2012)
Cueva Maripe (47°51´05´´S; 68°56´03´´ W; 560 masl) is located near a wetland identified as La Primavera in the Deseado Massif (Santa Cruz, Argentina). It is a large cave (26 m by 24 m) with two chambers separated by a rock wall (Miotti et al. 2004, 2007) (Figure 1). Its main walls and roof bear negative hand paintings (Carden 2008). The cave was occupied by humans recurrently from 9500 to 1000 14C rcybp, the earliest events in the southern chamber having been dated to 9518 ± 64 (AA-65175) and 8333 ± 63 rcybp (AA-65174), whereas in the northern chamber they took place at 8992 ± 65 (AA-65179) and 8762 ± 50 rcybp (AA-65178)(Miotti et al. 2007). The stratigraphy of Cueva Maripe shows a varied lithology in the 45 m2 excavated; different sedimentation rates and post-depositional processes in each sector affect the degree of preservation of archaeological materials. Agents including roof land sliding, waterlogging and water percolation in different parts of the cave, rodent activities, cattle trampling, a thick level of dung in surficial strata, and human activity until as late as a.d. 1950 have seriously impacted the archaeological context (Miotti et al. 2007). The main aims of this article are to determine the degree to which human activities or postdepositional processes in Maripe Cave have influenced the conservation of siliceous remains, and to understand the habitability conditions of each sector of the cave during different periods.